Bacterial-Based Strategies to Hydrolyze Gluten Peptides and Protect Intestinal Mucosa - Cristofori, Fernanda; Francavilla, Ruggiero; Capobianco, Daniela; Dargenio, Vanessa Nadia; Filardo, Simone; Mastromarino, Paola (Frontiers in Immunology, 2020)
Gluten is a mixture of proteins highly resistant to hydrolysis resulting in the emergence of toxic peptides responsible for gluten-related disorders. Currently, a gluten-free diet (GFD) is the unique proven effective treatment for celiac disease (CD). Several research groups and pharmaceutical companies are developing new non-dietetic therapeutic strategies for CD. Probiotics are viable microorganisms thought to have a healthy effect on the host. The proteolytic mechanism of lactic acid bacteria comprises an extracellular serine protease, di-and oligopeptide-specific transport systems and several intracellular peptidases that might affect gluten degradation. Therefore, probiotic supplementation is an attractive therapy because of its possible anti-inflammatory and immunomodulatory properties. Several studies have been performed to assess the effectiveness of various specific probiotic strains, showing positive effects on immune-modulation (inhibition of pro-inflammatory cytokine TNF-α) restoring gut microbiota and decrease of immunogenic peptides. The present review aims to summarize the current knowledge on the ability of probiotic strain (single or mixtures) to digest gliadin peptides in vitro and to modulate the inflammatory response in the gut.